Utilisation of Nitrogen by the Grape-vine as Affected by Time of Application and Soil Type - Conradie, W.J. (South African Journal of Enology and Viticulture, 2017)
Two-year-old Chenin blanc vines in sand culture were nurtured with 15N-labeUed nutrient solution at three different phenological stages, i.e. (1) between end of bloom and end of rapid shoot growth (spring), (2) between the end of rapid shoot growth and veraison (summer) and (3) post-harvest (autumn). The fate of the applied 15N was followed quantitatively over one year. In the spring and summer treatments, 43% of the labelled N was translocated to the bunches while only 22 % was still present as N reserves at the start of the next season. In the autumn treatment, however, 68 % of the labelled N was still present as reserves at the start of the next season. For the spring and summer treatments, migration of N from the leaves prior to leaf-fall and from the shoots prior to pruning, accounted for about 60% of the N reserves present at the start of the next season. Labelled N was also applied in the field during spring and autumn, using vines on sandy loam (20% clay) and sandy (8% clay) soils as test material. In the sandy loam soil about 30% of the labelled N from both the spring and autumn treatments was utilised by the vine up to the end of bloom in the following season. In the sandy soil about 50% of the labelled N was utilised by the vine during the same period. It is suggested that the higher utilisation of N on the sandy soil could be due to a lower content of organic matter. Less mineral N in the root zone of the sandy soil may cause a smaller dilution of applied N, giving rise to a larger fraction of applied N being utilised.